“ITULAH IBUMU” PENETAPAN KONSTITUTIF MARIA SEBAGAI BUNDA GEREJA: TELAAH BIBLIKAL ATAS TEKS YOH.19:25-27 - Dismas Turibius Neno; Siprianus Soleman Senda; Mikhael Valens Boy (Lembaga Penelitian STKIP Widya Yuwana, 2026)
One of the figures in the Bible who has an important role in the history of salvation is Mary. Mary's role began when she was called and chosen by God to conceive and give birth to the Word of God in the mystery of the Incarnation and her totality in accompanying Jesus in the work of His life until the fullness of Jesus'